Ag3VO4 / g-C3N4 / Bi2WO6 photocatalyst with efficient organic dye degradation and antibacterial activity
By constructing a Z-shaped heterojunction structure of Ag3VO4/g-C3N4/Bi2WO6, the problems of low photocatalytic efficiency and stability of Bi2WO6, g-C3N4 and Ag3VO4 photocatalysts were solved, achieving efficient degradation of organic dyes and antibacterial effects, meeting the needs of industrial applications.
Patent Information
- Application Number
- CN202411548509.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-01-07
AI Technical Summary
Existing Bi2WO6 photocatalysts have low photocatalytic efficiency, low photogenerated carrier transport efficiency and are prone to recombination, g-C3N4 has a small specific surface area and high recombination rate of photogenerated electron pores, and the stability of Ag3VO4 is affected by silver ion reduction. There is a lack of research on composite materials of these three materials, resulting in photocatalytic performance that fails to meet the needs of industrial applications.
By constructing a Z-shaped heterojunction structure of Ag3VO4/g-C3N4/Bi2WO6, flower-shaped Bi2WO6 was synthesized by solvothermal method and combined with fragmented g-C3N4. Rod-shaped Ag3VO4 was attached to g-C3N4/Bi2WO6 to form a double Z-shaped heterojunction, which promoted the separation of photogenerated electrons and holes. Ethylene glycol was used as a reducing agent to optimize the material parameters.
It achieves efficient degradation of organic dyes under visible light, with a degradation rate of 94.38% for RhB and 90.07% for MB. It also shows significant antibacterial effects under light irradiation, effectively prolonging carrier lifetime and improving the stability and activity of photocatalyst.
Smart Images

Figure CN119259102A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical fields of nano material preparation, environmental governance and new energy, and in particular to an Ag3VO4 / g-C3N4 / Bi2WO6 photocatalyst with high efficiency in degrading organic dyes and antibacterial activity. Background Art
[0002] With the depletion of non-renewable fossil fuels and the emergence of a series of problems such as the continuous deterioration of the environment, it has become urgent to find and develop renewable green energy. Photocatalytic technology is a new means that has gradually emerged in recent years to effectively improve the environment and energy. It is widely welcomed by researchers because of its green and pollution-free, large solar energy storage capacity, and no secondary pollution. However, photocatalysts generally have problems such as low transmission efficiency of photogenerated carriers and easy recombination, which makes photocatalytic technology cannot be truly applied to industries and life. Therefore, effectively improving the separation efficiency of photogenerated carriers at the semiconductor interface is helpful to design new and efficient photocatalysts. If it is possible to achieve the simultaneous occurrence of multiple effects such as photocatalytic degradation of dyes and photolysis of water, and achieve antibacterial while treating sewage, it will change the current situation of the sewage treatment process that only burns money but has no profit, further save costs, and avoid secondary pollution. It has broad application prospects in sewage treatment in printing and dyeing, pharmaceuticals, petrochemicals, papermaking, publishing and other industries, as well as in industrial and agricultural production such as removal and degradation of pesticides.
[0003] In recent years, the new photocatalyst Bi2WO6 has attracted close attention from researchers due to its suitable band gap, low price and layered structure. Bi2WO6 is a perovskite layered semiconductor photocatalyst, which consists of WO6 layers (with two [O] 2- and 1 [WO2] 2+ ) and [Bi2O2] 2+Because of its long-lasting visible light absorption ability and anti-photocorrosion ability, it is widely used in the field of light and optoelectronics. As a kind of ternary oxide semiconductor, Bi2WO6 nanomaterial has the advantages of high catalytic activity, simple preparation process, low environmental toxicity, good stability, faster electron-hole separation rate and more active sites. Its potential applications in environmental governance and energy conversion have been widely studied. Although Bi2WO6 photocatalysts have shown excellent performance in photocatalytic reactions, their photocatalytic efficiency still needs to be improved. In order to further improve the photocatalytic performance of Bi2WO6 photocatalysts and meet the requirements of practical applications under sunlight, it is still necessary to continue to improve its light absorption ability, separation and transportation efficiency of photogenerated carriers, and exposure of active sites. In Bi2MO6 (M=Mo, W) photocatalysts, Bi2WO6 and Bi2MoO6 both have Aurivillius layered structures. As a new type of visible light photocatalyst, the band gap widths of Bi2WO6 and Bi2MoO6 were experimentally measured to be 2.75 and 2.6 eV, respectively. The width of the band gap is not the only indicator for evaluating photocatalytic activity. For example, Bi2WO6 has a higher photocatalytic activity than Bi2MoO6 because Bi2WO6 has a larger specific surface area and a higher separation rate of photogenerated electrons and photogenerated holes than Bi2MoO6.
[0004] g-C3N4 has the advantages of suitable band gap (2.80eV) and conduction band (-1.26eV) position, low cost, non-toxicity, good stability, etc. At the same time, bulk g-C3N4 still has the disadvantages of small specific surface area, high recombination rate of photogenerated electron-hole pairs, and low visible light utilization, which limits its application.
[0005] Ag3VO4 (band gap of about 2.26 eV) is a silver-based photocatalyst with high degradation activity for organic pollutants under visible light irradiation. However, the carrier recombination rate of pure Ag3VO4 photocatalyst is inevitably too high. In particular, during the photocatalytic degradation process, the silver ions (Ag + ) is gradually reduced to silver (Ag). Excessive Ag will hinder the active sites of Ag3VO4, which will greatly reduce the stability of Ag3VO4 and thus reduce its photocatalytic performance. In order to solve these problems and improve the activity of the catalyst, morphology modulation, heterojunction construction, and precious metal doping are generally used. Bi2WO6, as a new type of photocatalyst, has a wider light absorption, a larger specific surface area, and a higher oxidation capacity. It is suitable for constructing a heterojunction with g-C3N4, and then Ag3VO4 is compounded with g-C3N4 / Bi2WO6 to enhance the stability of Ag3VO4 and construct a typical Z-type heterojunction, which effectively avoids the recombination of electrons and holes, enhances the absorption capacity of visible light, and can effectively improve its photocatalytic performance.
[0006] In view of the outstanding characteristics of photocatalysts and their own performance advantages, in recent years, although the research on Ag3VO4, g-C3N4 and Bi2WO6 has gradually increased, the morphology and performance of the synthesized ones are also different. However, there are almost no reports on the ternary composite of Ag3VO4, g-C3N4 and Bi2WO6. For example, Li et al. prepared Ag3VO4 / Bi2WO6 composite photocatalysts with different molar ratios of Ag3VO4 and Bi2WO6 by solvothermal method. When the molar ratio of Ag3VO4 to Bi2WO6 is 0.15:1, the Ag3VO4 / Bi2WO6 composite material has the best performance in photocatalytic degradation of Rhodamine B, and the RhB degradation rate constant is as high as 0.0392min -1 [S.Li et al. Journal of Colloid and Interface Science, 501 (2017) 156-163]. Mei et al. prepared porous g-C3N4 / Ag3VO4 composite materials by simple chemical deposition method and tested the photocatalytic performance of the composite materials by visible light catalytic degradation of methylene blue (MB). The results showed that g-C3N4 / Ag3VO4 with a g-C3N4 content of 40% had the best photocatalytic activity, and the MB degradation rate reached 99.3% after 8 minutes [F.Mei, et al. Applied Surface Science 488 (2019) 151-160].
[0007] Although the preparation of Bi2WO6, melamine-sintered g-C3N4, and g-C3N4 / Bi2WO6 composite materials have been reported, it may be easy for researchers in this field to combine Ag3VO4, g-C3N4 or Bi2WO6, but it is unknown whether ideal photocatalytic performance can be obtained. It is precisely because of this that in the literature reports on catalysts of these three components, only g-C3N4 / Bi2WO6 composite materials are relatively widely reported, and the related reports of the other two combinations are very rare, and the related content of the three-component Z-type heterojunction has not been reported yet. Taking these technologies into consideration, the artificial design and construction of Z-type heterojunction not only promotes the effective separation of electrons and holes, but also retains the excellent redox ability of the semiconductor conduction band and valence band. First of all, from the morphology of the material, the flower-ball-shaped Bi2WO6 material is fused with a thin layer of g-C3N4 and then combined with the rod-shaped Ag3VO4. This structure has a higher specific surface area and more active sites, which is more conducive to further modification and assembly of guest components; secondly, from the material preparation method, the solvothermal method is used to synthesize the flower-ball-shaped Bi2WO6 as a precursor, which is the prerequisite for obtaining this material; in addition, the material dosage, hydrothermal reaction temperature, hydrothermal time and other parameters are also obtained through our repeated exploration. More importantly, the Ag3VO4 / g-C3N4 / Bi2WO6 photocatalyst prepared by the present invention constructs a typical Z-type heterojunction structure, which promotes the separation of photogenerated electrons and holes.
[0008] Although the material composition obtained by the present invention is similar to many related studies, the material morphology prepared by the present invention is special, and the energy level structure and material structure are carefully designed, so as to achieve dye photodegradation and antibacterial, resulting in the excellent and unique properties of the photocatalytic material prepared by the present invention. The material preparation process parameters are determined one by one after a long period of careful exploration, so the product morphology of the present invention is novel, the product performance is advanced and unique, and the preparation method is original. The prepared material has extremely broad application prospects in many fields such as photocatalytic degradation of organic pollutants, photolysis of water to produce hydrogen, gas-sensitive devices, luminescent matrix materials, semiconductor sensors, etc. The material synthesis method explored by the present invention provides a precedent for the preparation of other composite materials and the synthesis of other semiconductor materials. Summary of the invention
[0009] The present invention prepares an Ag3VO4 / g-C3N4 / Bi2WO6 photocatalyst that can efficiently degrade organic dyes and has antibacterial effects. The catalyst is characterized in that the main body of the catalyst is a flower ball-shaped Bi2WO6, which is combined with broken flake g-C3N4, and rod-shaped Ag3VO4 is attached to the g-C3N4 / Bi2WO6 binary structure, forming a typical double Z-type heterojunction structure. In this double Z-type mechanism, electrons on the conduction bands of Bi2WO6 and Ag3VO4 are transferred to the valence band of g-C3N4 and recombine with holes on the valence band of g-C3N4, which allows electrons to be retained in the conduction band of g-C3N4, holes to be retained in the valence bands of Bi2WO6 and Ag3VO4, and photogenerated electrons in the conduction band of g-C3N4 are generated. - Shows a ratio of O2 / ·O2 - Potentials with more negative standard reduction potentials can reduce adsorbed O2 to O2 - , for the oxidation of MB. Photogenerated H in the valence band of Bi2WO6 and Ag3VO4 + Direct oxidation of H2O molecules generates OH radicals that react with organic dyes in water and play a degrading role in organic dyes. The proposed double Z transfer mechanism provides two transmission channels and prolongs the carrier lifetime. It not only promotes the transfer of electron-hole pairs, but also maintains a strong reduction / oxidation ability. Under visible light irradiation, the degradation rate of RhB by the catalyst is as high as 94.38% within 40 minutes, and the degradation rate of MB within 15 minutes reaches 90.07%. In addition, thanks to the construction of the double Z-type heterojunction, the separation and transfer of photogenerated electrons and holes are promoted, generating a large number of active groups. The catalyst can also achieve photocatalytic antibacterial performance under visible light. Using Escherichia coli without catalyst as a comparison, almost no Escherichia coli survival was observed in the sample with catalyst after 60 minutes of visible light irradiation, proving that it has a good antibacterial effect.
[0010] The photocatalyst designed by the present invention is realized as follows: the solvothermal method is used to synthesize Bi2WO6 as a precursor, which is the prerequisite for obtaining the material, and ethylene glycol is used as a reducing agent; in addition, parameters such as material dosage, hydrothermal reaction temperature, and hydrothermal time also directly affect the structure and photocatalytic performance of the prepared material. The method of the present invention is rich in resources, cheap in raw materials, simple in operation, and high in efficiency. The specific steps are:
[0011] (I) Solvothermal synthesis of pure bismuth tungstate precursor
[0012] The synthesis of Bi2WO6 precursor uses Bi(NO3)3·5H2O as bismuth source and sodium tungstate dihydrate (Na2WO4·2H2O) as tungsten source. The specific synthesis steps are as follows:
[0013] (1) Accurately weigh 0.1-5 g Bi(NO3)3·5H2O and dissolve it in 10-30 mL ethylene glycol solution, and stir it evenly on a magnetic stirrer;
[0014] (2) Dissolve 0.05-5 g Na2WO4·2H2O in 10-30 mL deionized water;
[0015] (3) Slowly add the obtained sodium tungstate solution into the Bi(NO3)3·5H2O solution dissolved in ethylene glycol and continue stirring until it is uniform;
[0016] (3) the resulting suspension was poured into a Teflon-lined hydrothermal kettle, placed in an oven and heated at 100-200°C for 8-18h;
[0017] (4) cooling naturally to room temperature, washing the product (denoted as BWO) and drying it at 50-60°C for 12-48h;
[0018] (II) Synthesis of g-C3N4 / Bi2WO6 composite photocatalyst
[0019] (1) Place melamine in a covered crucible and heat at 5-15°C min -1 Ramp rate to 300-500°C, heat for 2-5h, then cool to 20-30°C;
[0020] (2) collecting the light yellow product and grinding it into powder using agate mortar to obtain the final product g-C3N4 (expressed as CN);
[0021] (3) After mixing Na2WO4·2H2O and Bi(NO3)3·5H2O and stirring for 10-120 min in the above step, the prepared g-C3N4 is added to the mixed solution and continued to stir;
[0022] (4) The mixed solution is placed in a reaction kettle, heated in an oven at 100-200° C. for 10-20 h, and then taken out and naturally cooled to room temperature;
[0023] (5) The obtained mixed solution is filtered, and the filtered product is dried in a drying oven at 50-60° C. for 12-48 h to obtain a g-C3N4 / Bi2WO6 composite material photocatalyst.
[0024] (III) Synthesis of Ag3VO4 / g-C3N4 / Bi2WO6 composite photocatalyst
[0025] (1) Accurately weigh 0.1-5 g C3N4 / Bi2WO6 and dissolve it in 10-50 mL deionized water, and stir it evenly on a magnetic stirrer;
[0026] (2) Accurately weigh 0.04-5 g of AgNO3 and add it to the above solution, and stir it in a dark room for 30-120 min;
[0027] (3) Accurately weigh 0.02-3 g of Na3VO4 and dissolve it in 10-30 mL of deionized water. Slowly drip the resulting solution into the above mixed solution and continue stirring in a dark room for 30-120 min.
[0028] (4) Filter the mixed solution, and dry the filtered product in a drying oven at 50-60° C. for 12-48 h to obtain a Ag3VO4 / g-C3N4 / Bi2WO6 composite material photocatalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is the SEM photo of Ag3VO4 / g-C3N4 / Bi2WO6 ternary composite material;
[0030] Figure 2 It is the TEM image of Ag3VO4 / g-C3N4 / Bi2WO6 ternary composite material;
[0031] Figure 3 It is the XRD spectrum of Ag3VO4 / g-C3N4 / Bi2WO6 ternary composite material;
[0032] Figure 4 This is the degradation rate curve of the organic pollutants RhB and MB photodegradation by the Ag3VO4 / g-C3N4 / Bi2WO6 ternary composite material, which also serves as the abstract illustration. DETAILED DESCRIPTION
[0033] The Bi(NO3)3·5H2O, Na2WO4·2H2O, AgNO3, Na3VO4, melamine and ethylene glycol used in the present invention are all commercially available analytically pure products, and the deionized water is homemade in the laboratory; the glass instruments and equipment used are commonly used instruments and equipment in laboratories.
[0034] Example:
[0035] 0.291 g Bi(NO3)3·5H2O was dissolved in 15 mL ethylene glycol solution and stirred for 30 min. 0.105 g Na2WO4·2H2O was dissolved in 15 mL deionized water and the resulting solution was added dropwise to the above solution and stirred at 500 r·min. -1 The suspension was then poured into a 50 mL Teflon-lined hydrothermal kettle, placed in an oven and heated at 180°C for 14 h. Afterwards, it was cooled naturally to room temperature, and the product (denoted as BWO) was washed and dried at 60°C for 10 h.
[0036] Semiconductor g-C3N4 is produced by thermal polycondensation. Melamine is placed in a covered crucible and heated at 10 °C min -1 The temperature was raised to 500°C at a ramp rate for 4 h and then cooled to 25°C. The light yellow product was collected and ground into powder using an agate mortar to obtain the final product (denoted as CN). The theoretical loading amount of g-C3N4 was 5 wt% dispersed in the solution of synthesized BWO and ultrasonicated for 30 min to make the g-C3N4 dispersed uniformly. The product (5CN / BWO) was synthesized by solvothermal method.
[0037] Finally, Ag3VO4 / g-C3N4 / Bi2WO6 composites were synthesized by room temperature precipitation method. In short, a certain amount of g-C3N4 / Bi2WO6 and different proportions of AgNO3 were ultrasonically dissolved in 50mL deionized water, magnetically stirred for 30min under dark conditions, and then 10mL of Na3VO4 solution was added and stirred for 60min under dark conditions. Finally, the precipitate was washed and dried at 60℃ for 10h to obtain Ag3VO4 / g-C3N4 / Bi2WO6 composites.
[0038] Scanning electron microscope images of ternary Ag3VO4 / g-C3N4 / Bi2WO6 composite materials are shown in Figure 1 As shown in the photo, it can be seen that the prepared material is a fusion of flower-shaped Bi2WO6 with a diameter of about 1-2μm and g-C3N4, and then combined with rod-shaped Ag3VO4 with a diameter of about 0.5μm. This close interface contact is conducive to the separation and transfer of carriers in photocatalysis; Figure 2 The TEM image of the ternary Ag3VO4 / g-C3N4 / Bi2WO6 composite material shows that there is a large amount of Ag3VO4 on the prepared material petals; the X-ray diffraction analysis results of the prepared ternary Ag3VO4 / g-C3N4 / Bi2WO composite material are shown in Figure 3 As shown, by comparing with the standard card, it can be seen that the prepared materials are mainly tetragonal Bi2WO6 and hexagonal Ag3VO4 structures; Figure 4The degradation rate curve of MB and RhB degradation using Ag3VO4 / g-C3N4 / Bi2WO6 composite as catalyst is shown in Figure (a). After the catalyst reaches the adsorption equilibrium in dark treatment, the degradation rate of MB is as high as 90.07% within 15 minutes of illumination. After the catalyst reaches the adsorption equilibrium in dark treatment, the degradation rate of RhB reaches 94.38% within 40 minutes. In addition, antibacterial experiments were conducted. In the absence of catalyst, when the illumination time was 0 minutes, 20 minutes, 40 minutes and 60 minutes respectively, we found that the number of bacteria was almost not reduced. This shows that light has no bactericidal effect on Escherichia coli; after adding the catalyst, when the illumination time is 0min, 20min, 40min and 60min respectively, the number of bacteria is constantly decreasing, which shows that the Ag3VO4 / g-C3N4 / Bi2WO6 catalyst has an antibacterial effect on Escherichia coli under light, indicating that the prepared ternary Ag3VO4 / g-C3N4 / Bi2WO6 composite material will have great application prospects in the field of photodegradation of pollutants and antibacterial.
[0039] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, those skilled in the art may make various corresponding changes and modifications based on the present invention, but these corresponding changes and modifications should all fall within the scope of protection of the claims attached to the present invention.
Claims
1. A Ag3VO4 / g-C3N4 / Bi2WO6 photocatalyst with high efficiency in degradation of organic dyes and antibacterial activity, characterized in that: The morphology of the prepared Ag3VO4 / g-C3N4 / Bi2WO6 photocatalyst is mainly flower-ball-shaped Bi2WO6, which is combined with broken flake g-C3N4. Rod-shaped Ag3VO4 is attached to the g-C3N4 / Bi2WO6 binary structure, constructing a typical double Z-type heterojunction structure, which allows electrons to be retained in the conduction band of g-C3N4 and holes to be retained in the valence bands of Bi2WO6 and Ag3VO4, achieving effective separation of photogenerated electrons and holes while ensuring photogenerated The electrons are located at the energy level with the highest reduction potential, while the photogenerated holes are located at the energy level with the highest oxidation potential, achieving efficient photocatalytic performance of the prepared material. Under visible light irradiation, the degradation rate of the catalyst for RhB is as high as 94.38% within 40 minutes, and the degradation rate of MB is as high as 90.07% within 15 minutes. After 60 minutes of visible light irradiation, almost no E. coli survival is observed in the culture dish; the preparation method of Ag3VO4 / g-C3N4 / Bi2WO6 photocatalyst is as follows: (1) Preparation of Z-type g-C3N4 / Bi2WO6 precursor by combining high temperature solid phase method and solvothermal method Accurately weigh 0.1-5g of Bi(NO3)3·5H2O and dissolve it in 10-30mL of ethylene glycol solution, stir it evenly on a magnetic stirrer, accurately weigh 0.05-5g of Na2WO4·2H2O and dissolve it in 10-30mL of deionized water, slowly add the obtained Na2WO4 aqueous solution to the above-mentioned Bi(NO3)3 ethylene glycol solution, stir it evenly, then add g-C3N4 to the above-mentioned mixed solution in different mass ratios, stir it continuously for 0.5-3 hours, transfer it to an inner autoclave, hydrothermally treat it at 100-200℃ for 8-18 hours, cool it to room temperature, wash it by centrifugation, and dry it at 50-60℃ for 12-48 hours to obtain a g-C3N4 / Bi2WO6 precursor; (2) Synthesis of double Z-type Ag3VO4 / g-C3N4 / Bi2WO6 composite photocatalyst Accurately weigh 0.1-5g of g-C3N4 / Bi2WO6 precursor and disperse it in 10-50mL deionized water, add 0.04-5g of AgNO3, and stir in a dark room for 30-120 minutes. Accurately weigh 0.02-3g of Na3VO4 and dissolve it in 10-30mL of water, add the Na3VO4 solution dropwise into the mixed solution of g-C3N4 / Bi2WO6 and AgNO3, and continue stirring in a dark room for 30-120 minutes. The obtained precipitated product is separated by centrifugation, washed with deionized water and ethanol for many times, and dried at 50-60°C for 12-48 hours to obtain the composite material Ag3VO4 / g-C3N4 / Bi2WO6.